Family Farmers in Short and Long Marketing Channels: Lessons for Rural Development in Goiás, Brazil - Thiago de Carvalho Verano; Carlos de Melo e Silva Neto; Gabriel da Silva Medina (Logistics)
Background: Family farmers’ access to markets is key for rural development. This study seeks to assess to what extent short and long marketing channels promote or inhibit the commercial inclusion of family farmers. Methods: The research was conducted in the Brazilian state of Goiás through questionnaires and interviews with rural outreach agents and family farmers’ leaders. Results: The results reveal that 31.28% of sampled farmers are not included in any marketing channel. High inclusion rates in long channels (such as commodity markets) are related to high inclusion rates in short channels (such as farmers’ markets), with some regions having greater availability of marketing channels than other regions. Conclusions: The high participation of family farmers in long channels linked to the cattle supply chain and agricultural commodities is related to the low participation of this category in other channels. Such results provide lessons for public policies by demonstrating the need to encourage a greater diversity of both short and long channels to greater marketing opportunities for family farmers.